A new species of Ischnocnema lactea series (Anura: Brachycephalidae) from the highlands of Serra do Caparaó, Atlantic Forest, southeastern Brazil - Silva-Soares, Thiago; Campos, Natalia Soares; Pirovani-Silva, Erlan; Costa, Leonora Pires; Monjardim, Marina (Zootaxa, 2026)
A new species of frog from the Ischnocnema lactea series is described from Serra do Caparaó mountain range, state of Espírito Santo, southeastern Brazil. It is a small robber frog characterized by distinct red coloration on its fingers and toes, as well as on its concealed areas of inguinal region, thigh, tibia, and tarsus. The description of the new species is based on morphological and mtDNA data, and it is placed within the I. lactea species series with high support values. Phylogenetic analyses place the new species as a sister species to I. bocaina and I. spanios, confirming its membership in the I. lactea series. The species was discovered at montane elevations in the Caparaó National Park, a region of great ecological significance as a remnant of the critically endangered Atlantic Forest biome. The discovery of this tiny new species highlights the biological richness of the Caparaó highlands and reinforces the importance of ongoing conservation efforts in this biodiversity hotspot.